Promoting teacher candidates: self-efficacy through professional learning activities: towards equity and quality teacher training - Suleiman, Mahmoud. California State University, Fresno. Kremen School of Education and Human Development. Department of Educational Leadership; Schultz, Randy. California State University, Fresno. Kremen School of Education and Human Development. Department of Educational Leadership; Suleiman, Mahmoud; Schultz, Randy; Suleiman, Mahmoud; Schultz, Randy (Center for Leadership Equity and Research)
This paper examines teacher candidates efficacy through enhanced teacher education programs and rigorous professional learning engagements. Building on the axioms of equity, social justice and pluralism, reforming teacher preparation programs in urban settings is explored along with key reform elements (such as culturally responsive pedagogy, working with English Language Learners, Universal Design of Instruction, co-teaching and the like) that should be systematically and purposefully integrated. Using an action research approach, this paper reports preliminary findings revealed from longitudinal data collected from multiple sources within the context of a federally funded Edvention Partners Teacher Quality Grant. The programs functions and activities are described based on the current trends and practices along with social forces and demographic trends affecting schools today. Key reform elements necessary for effective teacher preparation programs and teacher efficacy are examined. Implications for enhancing teacher preparation programs are drawn along with workable strategies necessary for sustaining quality professional development opportunities.